2020
DOI: 10.1070/sm9189
|View full text |Cite
|
Sign up to set email alerts
|

Integrable billiard systems realize toric foliations on lens spaces and the 3-torus

Abstract: An integrable billiard system on a book, a complex of several billiard sheets glued together along the common spine, is considered. Each sheet is a planar domain bounded by arcs of confocal quadrics; it is known that a billiard in such a domain is integrable. In a number of interesting special cases of such billiards the Fomenko-Zieschang invariants of Liouville equivalence (marked molecules ) turn out to describe nontrivial toric foliations on len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Vedyushkina [43] constructed books with Q 3 belonging to the complement of the class of Seifert manifolds to the class of Waldhausen graph manifolds [44], [45], so that for billiard systems the class of isoenergy surfaces Q 3 is not confined to Seifert manifolds. A number of recent results was also discussed in [46]- [48].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Vedyushkina [43] constructed books with Q 3 belonging to the complement of the class of Seifert manifolds to the class of Waldhausen graph manifolds [44], [45], so that for billiard systems the class of isoenergy surfaces Q 3 is not confined to Seifert manifolds. A number of recent results was also discussed in [46]- [48].…”
Section: Introductionmentioning
confidence: 98%
“…Integrable flows on a sphere and a torus were modelled by Vedyushkina and Fomenko [55], [46] by means of integrable circular topological billiards (for a linear first integral) and confocal topological billiards and billiard books (for a quadratic first integral). With each such flow defined by a non-trivial Riemannian metric they associated a piecewise planar table with plane metric inside 2-cells, and with these planar parts glued isometrically along their boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Fomenko, Vedyushkina and Kibkalo investigated the 'local' version of the general conjecture (see [21]): they showed that arbitrary values of the marks r and ε on an edge of a molecule (see [22]) and the integer mark n on a family subgraph (see [23]) can be realized, as well as certain combinations of marks (see [24]). Also, an isoenergy surface Q 3 of a billiard book was shown to be homeomorphic to a 3-manifold [25], and billiards were constructed for which Q 3 is homeomorphic to a 3-torus, an arbitrary lens space L(q, p) for coprime p and q, 0 < p < q (see [26]), or a connected sum of arbitrary lens spaces L(q i , p i ) and products S 1 × S 2 (see [27]). As a result, for a billiard system Q 3 is not necessarily a Seifert manifold: one example is the connected sum of three lens spaces L(2, 1) (which are homeomorphic to the three-dimensional projective space).…”
Section: § 1 Introductionmentioning
confidence: 99%